Representations of Race, Gender and Ability in School Photography - Eric Margolis (Arizona State University, 2000)
This article examines photographs taken of American public school classes between the 1880's and the 1940's. Most of the images were found in two virtual archives: The American Memory site at the Library of Congress and The National Archives and Record Center. These very large photograph collections were searched for representations of race, gender, and physical ability. The photographs were compared and contrasted and analyzed for elements of hidden curricula using techniques drawn from the social sciences and humanities. It was found that these large photo collections have significant gaps and historical amnesias. Collections made under conditions of racial segregation are themselves segregated and continue to reproduce images of hierarchy and dominance. To the extent these sites function as important resources for teachers and students searching for primary source documents for history and social studies projects, the archives convey significantly biased views of the history of education and minority groups in America.